A Multiparentalidade como garantia do direito à origem na adoção de crianças e adolescentes em acolhimento institucional - Junqueira, Luciana Villela (2017)
In the light of the constitutional principles of Family Law and the interlocution with the theoretical and ethical-political foundations of Social Work, this doctoral thesis problematizes the reception of the so-called Multi-parenting, a jurisprudential and doctrinal "invention" recently raised to promote the preservation of Biological and affective affiliations, thus relativizing the need to break the origin ties. Although it represents a contradiction of classes that develops in the capitalist mode of production as a condition for the existence of the regime itself, the poverty and anti-personification of thousands of Brazilian families are still taken individually, authorizing the deprivation of the family coexistence of children and adolescents, as well as the use of adoption as a more effective and immediate protective measurement. The full adoption, duly preceded by the deprivation of family power, foresees the total and indeclinable collapse of the biological bonds, promoting not only the rupture of the paternal / maternal-filial relation, but, consequently, of the totality of the parental connections, sometimes deconstructing bonds of affection, of belonging and strengthening the relations of abandonment. The originating connections are constituents of the human personality and help to compose the identity of each one of us throughout the life. They tell stories of joys, separations, conflicts, affections, adding each of these elements in our psychic and affective structure. The absence of these places, of these people, and of the relations established there, provokes perennial marks in the one who experiences this experience of emptiness. In the light of the three-dimensional theory of family law that considers the integration of the affective, biological and ontological worlds, biological and socio-affective parenting could coexist in the children's rights sphere, ensuring the multiplicity of affections, the right to extended family life and all other developments in the protection of affiliation? It would be, therefore, a beneficial measurement that authorizes the change of the birth register to make it have all those persons who contributed to its formation and life history, besides giving them the rights of filiation of both parenting? In a recent decision, by equating the biological and affective affiliations, recognizing the importance of each of them for the preservation of fundamental human rights, the Federal Supreme Court set a historical precedent for re-discussion of this issue, allowing new forms of "Being" in the family can be accepted as an expression of human complexity